New Research and Trends in Higher Education - Sousa, Maria José; Suleman, Fátima; Mercadé Melé, Pere; Molina Gómez, Jesús (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book aims to discuss new research and trends on all dimensions of Higher Education, as there is a growing interest in the field of Higher Education, regarding new methodologies, contexts, and technologies. It includes investigations of diverse issues that affect the learning processes in Higher Education: innovations in learning, new pedagogical methods, and new learning contexts.In this sense, original research contributions of research papers, case studies and demonstrations that present original scientific results, methodological aspects, concepts and educational technologies, on the following topics:a) Technological Developments in Higher Education: mobile technology, virtual environments, augmented reality, automation and robotics, and other tools for universal learning, focusing on issues that are not addressed by existing research;b) Digital Higher Education: mobile learning, eLearning, Game-based Learning, social media in education, new learning models and technologies and wearable technologies for education;c) Case Studies in Higher Education: empirical studies in higher education regarding digital technologies, new methodologies, new evaluation techniques and tools, perceptions of learning processes efficiency and digital learning best practice.